ANTECEDENTS AND CONSEQUENCES OF CARBON EMISSIONS’ DISCLOSURE: CASE STUDY OF OIL, GAS AND COAL COMPANIES IN NON-ANNEX 1 MEMBER COUNTRIES - Dody Hapsoro; Ambarwati Ambarwati (Journal of Indonesian Economy and Business (JIEB), 2018)
The purpose of this study is to determine the characteristics of companies that voluntarily disclose carbon emissions and to examine the economic consequences of the carbon emissions’ disclosure. Companies used in the sample are oil, gas and coal companies in non-Annex 1 member countries registered in the Osiris database. The observation period was from the commencement of the Kyoto Protocol's second commitment to date, or from 2013 to 2016. Measuring the carbon emissions’ disclosure is achieved by using a checklist developed from an information request sheet from the CDP (Carbon Disclosure Project). An assessment of the extent of the disclosure is made using the content analysis method. Company characteristics are proxied with leverage, profitability and firm age, while the economic consequences are proxied by using bid-ask spreads, the trading volume and share price volatility. The data analysis method used in this research is the Partial Least Square (PLS) method using the WarpPLS 4.0 application. Test results show that leverage, profitability and firm age have a positive effect on the carbon emissions’ disclosure. Furthermore, the test results show that carbon emissions’ disclosures have a positive effect on the trading volume and a negative effect on the bid-ask spreads and share price volatility. The above findings imply that firms with higher leverage, higher profitability and are older are more willing to reveal their carbon emissions’ disclosures. The more information that is contained in a carbon emissions’ disclosure, the more investors are interested in trading that company's shares, while the broader the carbon emissions’ disclosure is, the smaller the bid-ask spread and the less volatile the stock price are.